25 Paediatric home sleep apnoea testing: service audit. (23rd February 2023) - Davies, Matthew; Laverty, Aidan; Samuels, Martin
Abstract : Background: Home Sleep Apnoea Testing (HSAT) for the diagnosis of Obstructive Sleep Apnoea (OSA) in children has recently gained momentum. Technical quality of HSAT is paramount to interpretability, with published data indicating wide variation in quality (46-87% 1, 2 ). This audit aimed to assess the technical quality of HSATs performed at our Paediatric Trust. Standards: HSAT was performed in line with published American Academy of Sleep Medicine (AASM) standards. 3 Referral criteria specify non- syndromic children (2-17yrs) with clinical suspicion of OSA. In-laboratory quality standards were implemented to assess interpretability of each study. Minimum requirements were: total sleep time (TST) ≥ 4hrs, artefact-free SpO2 recording for ≥ 4hrs of TST, and signals required to score respiratory events (nasal flow and/or respiratory effort bands) for ≥ 4hrs of TST. Target interpretability score is ≥ 75%. Methods: All consecutively recorded HSATs between 03/12/2019-01/03/2022 were retrospectively evaluated for meeting referral criteria and their interpretability. Results: 97 HSATs were performed. Mean age 7.7 ± 4.3yrs (59% male). 80% of HSATs performed met referral criteria. Total interpretability was 76.3% with only a small difference identified between those performed on patients meeting referral criteria and those not (76.9% vs 73.7% respectively). Primary causes of uninterpretable studies were: intolerance of all sensors (26.1%), absence of SpO2 (26.1%), and insufficient signals required to score respiratory events (34.8%). Conclusion: Interpretability score met our predefined target. Majority of HSATs were performed in patients meeting referral criteria. Recommendations to address uninterpretable HSATs include: improved parental teaching, modify SpO2 sensor attachment policy, and implement psychosocial support techniques. References: G.G. et al. 2019. Journal of sleep research 2019;28 (6):e12856. M.M. et al. Sleep Medicine 2020;68 :146-152. R.B. et al. AASM 2020.